Data Mining Tools and Techniques for Big Data: A Review - Jatinder Verma (International Journal of Advanced Science and Technology, 2020)
Huge Data refers to monstrous arrangement of information which is unpredictable to overseenpertaining to customary submissions. These days, it incorporates gigantic, inexhaustible organized,semi-structure, and unstructured information just as shrouded information that are created andaccumulated from a few fields. Problem with overseeing Big Data incorporate separating, dissecting,imagining, sharing, stockpiling, moving and looking through such information. At present, thecustomary information handling apparatuses also, its applications are not fit for overseeing suchchanged information. In this way, creating viable and productive Big Data Mining methods. This,thus, has opened doors to utilize the misusing man-made consciousness strategies for Big Data on theboard. This study explores the best Big Data Mining procedures and their method of reasoningapplications in different therapeutic and logical domains.